EXPLORING SILENT MYOCARDIAL INFARCTION AND ITS ASSOCIATIONS IN TYPE 2 DIABETIC PATIENTS: A CROSS-SECTIONAL STUDY IN A HOSPITAL SETTING. - Jha, Sanjay Nath (Student's Journal of Health Research Africa, 2023)
Introduction: Insulin resistance or insufficient insulin production in the body causes diabetes mellitus type 2, which primarily affects adults. Numerous micro and macrovascular issues are linked to long-term diabetes mellitus type 2. The objective of this study was to determine the incidence of silent MI in unaffected individuals with diabetes mellitus through the utilization of exercise treadmill testing. Materials and Methods: The Darbhanga Medical College & Hospital Department of Medicine conducted this cross-sectional observational study. The study included 120 asymptomatic type 2 Diabetes Mellitus patients with normal resting electrocardiograms and no coronary artery disease. Patients with myocardial infarction (MI), heart failure, angina pectoris, or other chronic illnesses were excluded from the study. The treadmill test (TMT) utilizing the "Bruce protocol" and CASE/T2100 sr number GE MAC revealed silent myocardial infarction. Results: 11.8% had silent MI (positive TMT). TMT positive was substantially linked to advanced age, diabetes for more than ten years, dyslipidemia, and an HbA1c of more than 10%. In comparison to TMT-negative patients, TMT-positive patients were shown to have considerably higher levels of total cholesterol, LDL, and triglycerides. TMT-positive individuals had considerably lower HDL levels than TMT-negative patients. Conclusion: A considerable fraction of individuals with T2DM had asymptomatic CAD or silent myocardial infarction (11.8%). Silent MI was more common in diabetics who were obese, dyslipidemic, older, and had high HbA1c. TMT may be a straightforward, non-invasive method for spotting silent MI early on. Recommendations: Treadmill testing (TMT) should be used to screen asymptomatic type 2 diabetics for silent myocardial infarction, especially those who are older, obese, have had diabetes for more than ten years, or have dyslipidemia and high HbA1c levels. TMT can identify silent MI in this population non-invasively.